The interaction of a vortex ring with a sloped sediment layer: critical criteria for incipient grain motion - Munro, Richard J. (American Institute of Physics, 2012)
Experiments were performed to analyse the interaction between a vortex ring and a sloped sediment layer. Attention focussed on interactions under “critical” conditions, in which sediment motion was only just induced by the ring's flow field. Both hydraulically smooth and hydraulically rough bedforms were analysed, using near-spherical monodisperse sediments with relative densities of 1.2 and 2.5 and mean diameters (d p ) ranging between 80 and 1087 μm. Measurements of the vortex-ring flow field were obtained, during the interaction, using two-dimensional particle imaging velocimetry. The threshold conditions for incipient sediment motion were analysed in terms of the critical Shields parameter (N c ), defined in terms of the peak tangential velocitymeasured adjacent to the bed surface. Bed-slope effects were investigated by tilting the sediment layer at various angles between the horizontal and the repose limit for the sediment. In all cases, the propagation axis of the vortex ring was aligned normal to the bed surface. The measured values of N c were compared with a force-balance model based on the conditions for incipient grain motion on a sloping bed. For hydraulically smooth bedforms, where the bed roughness is small compared to the boundary-layer depth, the model was derived to account for how viscous stresses affect the drag and lift forces acting on the near surface sediment. For hydraulically rough bedforms, where this viscous-damping effect is not present, the model assumes the drag and lift forces scale with the square of the near-bed (inviscid) velocity scale. In both cases, the model predicts that bedforms become more mobile as the bed slope is increased. However, the damping effect of the viscous sublayer acts as a stabilizing influence for hydraulically smooth bedforms, to reduce the rate at which the bed mobility increases with bed slope. The measured values of N c were in agreement with the trends predicted by this model, and exhibit a transition in behaviour between the smooth-bed and rough-bed cases when d p /δ s ≈ 20 (where δ s is the viscous-sublayer length scale).